Self Hand Manipulation Using Su-Jok For Heartburn in Adults - Lu'Lu', Alvianita Ziinat; Billa, Azizah Salsa; Pertiwi, Alda Puspa; Fadhilah, Jihan; Dyaksa, Hadyan Marta; Yuliana, Rita; Isnuwardana, Ronny (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Functional dyspepsia affects 24–40% of adults in Indonesia and is frequently associated with heartburn. At the Lempake Community Health Center in Samarinda, heartburn ranked as the third most common outpatient complaint, with 765 reported cases between January and August 2024. This study aimed to evaluate the effectiveness of Su-Jok therapy as a complementary intervention for alleviating heartburn symptoms. A non-randomized trial without a control group was conducted among clinic patients. Data were collected through structured interviews and a Numerical Rating Scale (NRS) of pain, administered before and after the intervention in patients with non-complicated heartburn. The study included 22 respondents aged 19 to 55, of whom 75% were female. Analysis using the Wilcoxon test showed a statistically significant reduction in NRS scores following Su-Jok therapy (p < 0.001). These findings suggest that Su-Jok hand manipulation effectively reduces subjective heartburn symptoms and may serve as a practical initial or complementary treatment. Su-Jok therapy offers a non-invasive, accessible option for managing heartburn, potentially reducing symptoms before the need for further medical intervention.